Juridical review of criminal acts of environmental destruction that occurred in the tele forest, samosir regency - Sigar P. Berutu; Mazmur Septian Rumapea (LEGAL BRIEF, 2023)
This study aims to examine the environmental crimes that occurred in the forest area of ??Tele, Samosir Regency, with the background of the problem of how the regulation of criminal acts of environmental destruction is based on Law No. 32 of 2009; how efforts to overcome environmental crimes are based on Law No. 32 of 2009; and how the legal policy on environmental crimes is based on the decision of the District Court Number: 28/PID.SUS/PN.Blg. The research method used in writing this thesis is descriptive. The analysis leads to normative juridical material, namely another legal material. This research is an answer to the background of problems related to environmental crimes that occurred in the Tele forest, Samosir Regency.